Growth hormone secretion, fatigue and quality of life after childhood traumatic brain injury. Issue 3 (September 2019) - Daskas, N; Sharples, P; Likeman, M; Lightman, S; Crowne, E C
Abstract : Context: Traumatic brain injury (TBI) is a recognised cause of hypopituitarism in adults but the prevalence after childhood TBI remains controversial. Objective: To investigate long-term endocrine outcomes and quality of life (PedsQL and QoL-AGHDA (Quality of Life in Adult Growth Hormone Deficiency Assessment)) following childhood TBI. Design: Prospective study. Methods: Participants with moderate/severe TBI ( n  = 31) and controls ( n  = 17). Mean (range) age: 19.8 ± 4.2 (11–26), time post TBI: 9 (7–11) years. Detailed endocrine evaluation of stimulated (insulin tolerance test (ITT)) and spontaneous GH secretion (overnight profile) was undertaken in the TBI group; QoL and neuroimaging in both groups. Results: No participant had seizures, short stature, precocious puberty or hypothyroidism. In 6/25 the ITT GH response was below age-defined cut-offs and cortisol <500 nmol/L in 2/25. Mean spontaneous GH secretion was <3.1 µg/L in 16/22 but peak GH was low only in 1/22 profiles. One patient had abnormal spontaneous and stimulated GH secretion and hypogonadism. Fatigue and depression scores were higher in TBI patients ( P  = .011 and P  = .020). Fatigue correlated with measures of spontaneous but not stimulated GH secretion. Overall QoL (PedsQL) did not differ between groups but specific attributes of health state (cognition, memory) were impaired in TBI patients. Pituitary neuroimaging was normal in all participants. Conclusions: Fatigue and depression were common 8–10 years post childhood TBI. One individual had GHD (1/22) using rigorous diagnostic criteria. A single ITT potentially over-diagnosed GHD in 25% (6/25) without clear correlation with symptoms underlying the importance of using two diagnostic tests in TBI survivors.